Increased neointimal thickening in dystrophin-deficient mdx mice. - Uwe Rauch (Public Library of Science (PLoS), 2012)
Background The dystrophin gene, which is mutated in Duchenne muscular dystrophy (DMD), encodes a large cytoskeletal protein present in muscle fibers. While dystrophin in skeletal muscle has been extensively studied, the function of dystrophin in vascular smooth muscle is less clear. Here, we have analyzed the role of dystrophin in injury-induced arterial neointima formation. Methodology/principal findings We detected a down-regulation of dystrophin, dystroglycan and β-sarcoglycan mRNA expression when vascular smooth muscle cells de-differentiate in vitro. To further mimic development of intimal lesions, we performed a collar-induced injury of the carotid artery in the mdx mouse, a model for DMD. As compared with control mice, mdx mice develop larger lesions with increased numbers of proliferating cells. In vitro experiments demonstrate increased migration of vascular smooth muscle cells from mdx mice whereas the rate of proliferation was similar in cells isolated from wild-type and mdx mice. Conclusions/significance These results show that dystrophin deficiency stimulates neointima formation and suggest that expression of dystrophin in vascular smooth muscle cells may protect the artery wall against injury-induced intimal thickening.